2019
DOI: 10.21873/anticanres.13585
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Short-course Radiotherapy in Advanced Pelvic Cancer: A Phase II Study (SHARON Project)

Abstract: Aim: To define safety and efficacy of a palliative, short-course accelerated radiation therapy for symptomatic locally advanced primary pelvic cancer. Materials and Methods: A phase II trial was planned based on the minimax Simon's twostage design. A total of 18 Gy in 4.5 Gy/fraction administered twice a day was delivered (SHARON). Pain and quality of life were recorded according to the Visual Analogue self-assessment and the cancer linear analog scales (CLAS), respectively. Results: Twenty-five patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
1
9
0
1
Order By: Relevance
“…In pelvic cancer, the impact of palliative treatments on QoL is poorly studied. A recent pilot data set from 25 patients treated with radiotherapy where the baseline symptoms were pain (48%), bleeding (40%), bleeding/pain (8%), and intestinal sub-occlusion (4%) showed that the improvement in well-being was 64% and in ability to perform daily activities 48% [33], which mirrors the emotional and physical functioning metrics in our patient cohort.…”
Section: Discussionsupporting
confidence: 73%
“…In pelvic cancer, the impact of palliative treatments on QoL is poorly studied. A recent pilot data set from 25 patients treated with radiotherapy where the baseline symptoms were pain (48%), bleeding (40%), bleeding/pain (8%), and intestinal sub-occlusion (4%) showed that the improvement in well-being was 64% and in ability to perform daily activities 48% [33], which mirrors the emotional and physical functioning metrics in our patient cohort.…”
Section: Discussionsupporting
confidence: 73%
“…Among the published trials, 116 trials (52%) used PROs. PROs were primary end points in 45 trials 20,26,28,30,[34][35][36][37]42,48,53,[56][57][58][61][62][63]66,70,74,75,77,79,83,85,93,94,97,103,[108][109][110]113,115,117,118,124,125,127,128,130,133,134,137 (20% of all published trials; 31% of 145 trials clearly stating their primary end point; 39% of 116 trials including a PRO) and secondary end points in 71 trials 24,25,27,29,[31][32][33]…”
Section: Resultsmentioning
confidence: 99%
“…[ 26 ], or the bis-in-die (BID) schedules advised by both the “Quad Shot RTOG 8502–QUAD SHOT” report created by Spanos et al . [ 27 , 28 ] and the “Sharon project” for multiple palliative settings [ 31 ], can be highly useful. Moreover, our NORMALITY model suggests and offers forms to facilitate the enhancement of preliminary teleconsultations before the first clinical visits of the patients (Figs.…”
Section: Discussionmentioning
confidence: 99%